A participação dos contadores brasileiros na agenda esg - Souza, Priscila (Universidade Federal de São Carlos, 2024)
Accounting is a social science that follows changes in society and has the specific objective of assisting its users in decision-making. Its developments are in specific areas such as costs, taxes, management and environmental issues. The main objective of this work is to present the participation of Brazilian accountants in the ESG agenda, what relevant information is produced by the class, and how to demonstrate the environmental impacts caused by companies in Brazil. In addition to the participation or not of Brazilian accountants in the ESG agenda, this work sought to understand the studies on environmental accounting and whether it has become a path for the construction and insertion of ESG in Brazil. Much information has been disclosed about a responsible social culture on the part of companies, called new capitalism, and internal policies have also been applied and disclosed. This dissertation work arises from the questions raised about the effective measurement and application of ESG carried out by Brazilian accountants. To this in-depth study, we researched the disclosure of content in scientific journals in the accounting area. The selected journals were the Brazilian Accounting Journal, produced by the Federal Accounting Council, a representative body for the profession, the Accounting Education and Research Journal and the Accounting and Finance Journal, produced by FEA/USP in partnership with Fipecafi, which are institutions that support the practice of accounting professionals in Brazil. The research was based on a mixed qualitative and qualitative bibliographic methodology, verifying the scientific productions of accountants on the ESG agenda in Brazil. It was concluded that there are few studies and analyses from the accounting field itself about practical guidelines on ESG, demonstrating that it is still a subject under construction in Brazil.
The participation of brazilian accountants in the esg agenda
Keywords: Contabilidade; Esg; Ambiental; Cfc; Accounting; Environmental; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::CIENCIAS CONTABEIS